Why Do Entrepreneurial Parents Have Entrepreneurial Children? - Lindquist, Matthew J.; Sol, Joeri; Van Praag, Mirjam (Journal of Labor Economics, 2015)
We explore the origins of the intergenerational association in entrepreneurship using Swedish adoption data that allow us to quantify the relative importance of prebirth and postbirth factors. We find that parental entrepreneurship increases the probability of children’s entrepreneurship by about 60%. For adoptees, both biological and adoptive parents make significant contributions to this association. These contributions, however, are quite different in size. Postbirth factors account for twice as much as prebirth factors in our decomposition of the intergenerational association in entrepreneurship. We investigate several candidate explanations for this large postbirth factor and present suggestive evidence in favor of role modeling.